(untitled) - Hock, Randolph (Medford, N.J., 2007)
A phenomenal resource for both extreme and not-so-extreme researchers. Great tips, clear explanations, and years of expertise distilled into 250 pages of clear, engaging text. This book should be on every searcher's desk. — Mary Ellen Bates, coauthor, Researching Online for Dummies. Hock has established an enviable reputation for his series of books about search engines and online searching. They are always detailed, insightful, and up to date. This book continues that tradition of excellence. — Online Information Review. [Hock's] clear and useful guide will help anyone interested in going beyond Google, explaining when, why, and how best to use various search tools and other Web resources. — Library Journal
Keywords: Internet searching,Web search engines,Computer network resources,Web sites,Internet addresses; Handbooks, manuals, etc.,Handbooks, manuals, etc.,Handbooks, manuals, etc.,Directories,Directories